PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI KHUSUS, DAN DANA ALOKASI UMUM TERHADAP KINERJA KEUANGAN PEMERINTAH KOTA PROVINSI JAWA TENGAH TAHUN ANGGARAN 2020-2024 - Ricco Andhika Hudaya; Novan Setiawan; Aldinda Putri Nuraini; Fitri Nopitasari; Puji Lestari (CV. Denasya Smart Publisher, 2026)
Following fiscal decentralization, local governments are required to optimize budgetary autonomy to minimize reliance on the central government. This study examines the impacts of Regional Original Revenue (PAD), Special Allocation Funds (DAK), and General Allocation Funds (DAU) in constructing the Financial Performance of City Governments in Central Java Province throughout the 2020–2024 fiscal years. This quantitative investigation applies a census design (saturated sampling) encompassing all city governments (6 entities) within the Central Java region. Utilizing secondary panel data sourced from the Budget Realization Reports (LRA), this study yields 30 observation units evaluated through multiple linear regression analysis via the SPSS version 30 software. Partially, the test results confirm that PAD positively and significantly stimulates regional financial performance, aligning with Stewardship Theory. Conversely, due to the emergence of a fiscal comfort zone arising from substitution effects, DAU is detected to exert a significant negative influence. Meanwhile, the rigid nature of DAK as a specific grant prevents it from demonstrating any meaningful effect. Simultaneously, these three revenue posts contribute substantially to determining the Financial Performance of City Governments in Central Java Province during the 2020–2024 era. This study concludes that accelerating regional fiscal performance fundamentally demands progressive intensification of PAD and the efficient governance of balancing funds.